Molecular characterization and relatedness of Haematobia irritans (horn fly) populations, by RAPD-PCR - Castiglioni, L.; Bicudo, HEMD (Springer, 2005)
Haematobia irritans is a hematophagous parasite of cattle that causes significant economic losses in many parts of the world, including Brazil. In the present work, one American and four Brazilian populations of this species were studied by Random Amplified Polymorpht DNA (RAPD) to assess basically genetic variability within and between populations. Ten different decamer random primers were employed in the genomic DNA amplification, yielding 117 fragments in the five H.. irritans populations. In Drosophila prosaltans, used as an outgroup, 81 fragments were produced. Forty-three of these fragments were shared by both species. Among the H. irritans samples, that from Rio Branco (Acre State, Brazil) produced the smallest numbers of fragments and polymorphic bands. This high genetic homogenity may be ascribed to its geographic origin (in the Northwest of Brazil), which causes high isolation and low gene flow, unlike the other Brazilian populations, from the South Central region, in which cattle trade is very intensive. Marker fragments (exclusive bands) detected in every sample enabled the population origin to be characterized, but they are also potentially useful for further approaches such as the putative origin of Brazilian populations from North America. Similarity indices [Nei & Li, 1979, Proc. Natl. Acad. Sci. USA 76: 5269-5273] and phylogenetic trees, rooted by using the outgroup and produced by the Phylogenetic Analysis using Parsimony (PAUP 4.0-Swofford, 2001) program showed the closest relationships between flies from Sao Jose do Rio Preto and Turiuba (both from São Paulo State, Brazil) while flies from the geographically distant Rio Branco showed the greatest differentiation relative to the others.
Keywords: DNA markers; Haematobia irritans (horn fly); molecular relatedness; Polymorphism; RAPD-PCR